Uma análise da contribuição de sistemas de informação eletrônicos de recursos humanos nas organizações - Vladimir Alexei Rodrigues Rocha (2023)
Although the growing use of Electronic Human Resource Management (e-HRM) aims to contribute to making the Human Resources (HR) function more strategic in its activities, studies reveal that in many organizations, HR has not realized the benefit of achieving the transformative role of operating and contributing strategically – a role that e-HRM promises to provide. E-HRM is necessary for HR to play a strategic role, but it is not sufficient to make it a reality. For HR to become more strategic, it is suggested that HR needs to be able to use information from its e-HRM technology to initiate and support strategic decisions. At the same time, studies have shown difficulties in achieving a unified understanding of how this can happen. In this sense, this research has the overall objective of analyzing the contribution of Electronic Human Resource Management in organizations. To achieve this, specific objectives were defined, including the identification of factors that positively or negatively influence the adoption of e-HRM in organizations; an attempt to understand the mechanisms and social structures involved in the contribution of e-HRM to the organization; empirical identification of how HR practices are employed in e-HRM; and an analysis of the contribution characteristics of e-HRM, according to the degree of agreement of the defined constructs. A comprehensive literature review was conducted to identify related works and underlying results, with theoretical foundations in research involving Information Technology (IT) and Human Resource Management (HRM) such as Value Creation, Resource-Based View (RBV), Strategic Human Resource Management (SHRM), and Technology Acceptance Model (TAM). The methods employed to achieve the proposed objectives began with a philosophical perspective to understand the social phenomenon whose reality is constructed by the respondent; the research was characterized as mixed method, classified as descriptive, and applied in nature. A total of 106 participants were involved, with a non-probabilistic and convenience sample. A Likert-type questionnaire, consisting of both objective and subjective questions, was used as the data collection instrument in the methodology. Descriptive statistics and factor analysis were employed for the presentation and analysis of quantitative data. For qualitative questions, Bardin's content analysis was used. As a result, socio-economic factors showed a dominance of HR professionals in the age range of 36 to 45, academic background in Psychology, working in private organizations with more than 1,000 employees, and a dominance of 16 or more years of experience in HR. The dominance of the agreement variable of the "perception of managers' vision of e-HRM" factor was highlighted as having the greatest influence on the contribution to the organization, followed by the "perceived utility with the adoption of e-HRM." Among the analyzed frequency variables, the "implementation of HR practices in e-HRM" factor stood out. It was concluded that there is recognition of the importance of e-HRM in organizations; however, the focus tends to be more on automating administrative and operational activities rather than on the development of strategic partnerships and expanding the HR's capacity to act in organizations.